Developing ethyl formate treatment for disinfesting pipfruit - Jamieson, L.E.; Griffin, M.J.; Page-Weir, N.E.M.; Chhagan, A.; Redpath, S.P.; Connolly, P.G. (New Zealand Plant Protection, 2014)
Mealybugs scale insects thrips and apple leafcurling midge (ALCM) on packed New Zealand apples are a concern for export markets and there is interest in soft technologies to remove insects in postharvest treatments Ethyl formate (EF) is a Generally Recognised As Safe (GRAS) plant volatile compound which was used in trials to reduce pest incidence on apples to acceptable rates for export markets A treatment of 03 EF (CO2) for 1 h controlled 99 of onion thrips and latania scale and 081 EF (CO2) for 1 h controlled obscure mealybug Treatment concentrations and times required to control ALCM (494 EF for 4 h) was beyond the apple quality tolerance level Further research is required to determine apple quality tolerance levels other market access pest EF concentration mortality responses sorption rates of different apple cultivars and effect of temperature on pest mortality and fruit responses